Students' profiles of ICT use: Identification, determinants, and relations to achievement in a computer and information literacy test. (May 2017) - Scherer, Ronny; Rohatgi, Anubha; Hatlevik, Ove E.
Abstract: Current debates on students' use of information and communication technology (ICT) have brought to attention profiles and purposes of ICT use in either school-related or recreational contexts. Examining these two contexts at the same time, the present study seeks to identify student profiles of ICT use on the basis of the Norwegian International Computer and Information Literacy Study (ICILS) 2013 data ( N  = 2426). In order to explore profiles of ICT use in schools and at home for different purposes such as recreation, study purposes, exchanging information, and social communication, we take a person-centered approach and apply latent profile analysis. These analyses revealed two independent user profiles and showed that background characteristics (i.e., gender, immigration status) and motivational constructs (i.e., self-efficacy, interest, and enjoyment in ICT) play a significant role in determining profile membership. Significant differences between the user profiles in students' computer and information literacy test performance did not exist. Given that the coverage of ICT at home and in schools has increased substantially over the last decades, the identification of user profiles informs teachers and parents about whether or not students exploit these opportunities to the same extent. Implications for future research and practice are discussed. Highlights: Two latent profiles of students' ICT use were identified. Profile 1 describes students who stay low on leisure-related Internet activities. Profile 2 describes students who frequently use ICT for almost all purposes. Profile membership was related to immigration status, gender, and motivation. The profiles did not differ in students' communication and information literacy.